2019
DOI: 10.1186/s12964-019-0378-7
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibition drives anti-viral defence in RV but not RSV challenged human airway epithelial cells through AKT/p70S6K/4E-BP1 signalling

Abstract: Background The airway epithelium is a major target tissue in respiratory infections, and its antiviral response is mainly orchestrated by the interferon regulatory factor-3 (IRF3), which subsequently induces type I (β) and III (λ) interferon (IFN) signalling. Dual specificity mitogen-activated protein kinase kinase (MEK) pathway contributes to epithelial defence, but its role in the regulation of IFN response in human primary airway epithelial cells (AECs) is not fully understood. Here, we studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 74 publications
3
13
1
Order By: Relevance
“…While monitoring signaling changes in host cells, we observed activation of GFR signaling cascades after infection, consistent with other viruses relying on the receptors themselves or elicited signal transduction (Eierhoff et al, 2010;Kung et al, 2011;Lupberger et al, 2011;Ueki et al, 2013;Wu et al, 2017;Zhu et al, 2009). From our data we could not clearly conclude which GFR might be activated and thus tested whether GFR 235 downstream signaling inhibition can prevent SARS-CoV-2 replication, as reported for some other viruses (Baturcam et al, 2019;Pleschka et al, 2001).Previously, temporal kinome analysis identified antiviral potential of RAS/RAF/MEK and PI3K/AKT/ for MERS-CoV (Kindrachuk et al, 2015). By targeting the RAS/RAF/MEK and PI3K/AKT/mTOR downstream axes of GFR signaling, we found efficient inhibition of cytopathic effects and cell destruction (Figure 4).…”
Section: Discussionsupporting
confidence: 79%
“…While monitoring signaling changes in host cells, we observed activation of GFR signaling cascades after infection, consistent with other viruses relying on the receptors themselves or elicited signal transduction (Eierhoff et al, 2010;Kung et al, 2011;Lupberger et al, 2011;Ueki et al, 2013;Wu et al, 2017;Zhu et al, 2009). From our data we could not clearly conclude which GFR might be activated and thus tested whether GFR 235 downstream signaling inhibition can prevent SARS-CoV-2 replication, as reported for some other viruses (Baturcam et al, 2019;Pleschka et al, 2001).Previously, temporal kinome analysis identified antiviral potential of RAS/RAF/MEK and PI3K/AKT/ for MERS-CoV (Kindrachuk et al, 2015). By targeting the RAS/RAF/MEK and PI3K/AKT/mTOR downstream axes of GFR signaling, we found efficient inhibition of cytopathic effects and cell destruction (Figure 4).…”
Section: Discussionsupporting
confidence: 79%
“…The beneficial effect of MEK inhibitors on host defense may not be limited to bacterial infections as several reports suggest a direct or indirect antiviral effect on different respiratory viruses, including influenza 58,59 and rhinovirus. 60 The completion of the life cycle of influenza is dependent on the MEK pathway as it facilitates the nuclear export of the viral ribonucleoprotein. 61 We recently identified MEK as a key regulator of interferon response in airway epithelial cells and inhibition of MEK led to enhanced IFN response, which translated into a reduction of rhinovirus replication.…”
Section: Discussionmentioning
confidence: 99%
“…61 We recently identified MEK as a key regulator of interferon response in airway epithelial cells and inhibition of MEK led to enhanced IFN response, which translated into a reduction of rhinovirus replication. 60 Since these viruses are commonly associated with COPD exacerbations, the inhibition of MEK1/2 pathway may represent a new strategy for treating virus-induced exacerbations in COPD.…”
Section: Discussionmentioning
confidence: 99%
“…Downstream of IL-22 signaling, IL-22 primarily activates STAT3 (Baturcam et al, 2019;Edsbacker et al, 2019;Gimeno Brias et al, 2016;Mahony et al, 2017;Wolk et al, 2010) with STAT1 involvement in certain instances (Lejeune et al, 2002). To determine which of these pathways is involved in the inhibition of virus production by IL-22, we examined STAT1 and STAT3 activation status in the IL-22-treated A549 cells and observed that IL-22 triggered phosphorylation of both STAT1 and STAT3 to similar degrees (Figures 2A and 2B).…”
Section: Il-22 Prevents Rsv Production Through Stat3 Activationmentioning
confidence: 94%
“…Type I IFNs play a crucial role in host defense against viruses and upregulate several IFN-stimulated genes (ISGs) that play important roles in eliminating the virus from infected cells (Baturcam et al, 2019;Edsbacker et al, 2019;Mahony et al, 2017). In addition, type III IFNs (IFN-l) have been also implicated in anti-viral host defense (Kotenko, 2011).…”
Section: Il-22 Regulates Rsv Production Without Altering Expression Of Type I and Type Iii Interferonsmentioning
confidence: 99%